2017
DOI: 10.1186/s12863-017-0511-9
|View full text |Cite
|
Sign up to set email alerts
|

Candidate gene based association mapping in Fusarium culmorum for field quantitative pathogenicity and mycotoxin production in wheat

Abstract: BackgroundQuantitative traits are common in nature, but quantitative pathogenicity has received only little attention in phytopathology. In this study, we used 100 Fusarium culmorum isolates collected from natural field environments to assess their variation for two quantitative traits, aggressiveness and deoxynivalenol (DON) production on wheat plants grown in four different field environments (location-year combinations). Seventeen Fusarium graminearum pathogenicity candidate genes were assessed for their ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 114 publications
2
26
0
Order By: Relevance
“…However, studies searching for resistance QTL in wheat (Anderson et al, ; Buerstmayr et al, ) and aggressiveness in Fusarium spp. (Castiblanco et al, ; Talas et al, ) involved only one pathogen isolate (in the search of resistance) or one host genotype (in the search of aggressiveness). Here, we could show that the same isolates are able to infect all four host species without significant rank changes, thus demonstrating the broad‐spectrum expectation for this quantitative host–pathogen interaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies searching for resistance QTL in wheat (Anderson et al, ; Buerstmayr et al, ) and aggressiveness in Fusarium spp. (Castiblanco et al, ; Talas et al, ) involved only one pathogen isolate (in the search of resistance) or one host genotype (in the search of aggressiveness). Here, we could show that the same isolates are able to infect all four host species without significant rank changes, thus demonstrating the broad‐spectrum expectation for this quantitative host–pathogen interaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies searching for resistance QTL in wheat (Anderson et al, 2001;Buerstmayr et al, 2002) and aggressiveness in Fusarium spp. (Castiblanco et al, 2017;Talas et al, 2012) involved only one pathogen isolate (in the search of resistance) or one host genotype (in the search of aggressiveness).…”
Section: High Plasticity Also Observed For Colonization Of Differenmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these reports, no variety with adequate level of resistance to F. culmorum is currently available and research on genomic regions associated with resistance to F. culmorum has received no attention. Recently, a candidate gene-based association study reported association of mitogen-activated protein kinase (MAPK) HOG1 gene with aggressiveness and deoxynivalenol (DON) production, explaining 10.29 and 6.05% of the genotypic variance, respectively [ 35 ]. This present study aims to improve resistance of spring bread wheat to F. culmorum with the following objectives: (i) analyze resistance responses of spring bread wheat accessions to F. culmorum , and (ii) use GWAS to identify novel genomic loci conferring resistance to F. culmorum .…”
Section: Introductionmentioning
confidence: 99%
“…Fungal pathogenicity factors, including secreted cell-wall degrading enzymes, phytotoxins, and cell death-inducing proteins, have been described [89,101]. Certain isolates of F. culmorum produce the toxins nivalenol and deoxynivalenol, which contribute to yield losses caused by F. graminearum in Fusarium head blight of cereals [8,35,102,103]. A possible candidate for HIGS in F. culmorum arose from observations of developmental and metabolic defects associated with mutations in the StuA transcription factor gene [30].…”
Section: Host-induced Gene Silencing (Higs)mentioning
confidence: 99%